Kaolin-loaded chitosan/polyvinyl alcohol electrospun scaffold as a wound dressing material: in vitro and in vivo studies. (2nd May 2020) - Salehi, Majid; Farzamfar, Saeed; Ehterami, Arian; Paknejad, Zahrasadat; Bastami, Farshid; Shirian, Sadegh; Vahedi, Hamid; Koehkonan, Gholamreza Savari; Goodarzi, Arash
Abstract : Objective: To evaluate the application of a fabricated dressing containing kaolin for skin regeneration in a rat model of excisional wounds. Method: In the present study, kaolin was loaded into electrospun polyvinyl alcohol (PVA)/chitosan polymer blend to develop a composite nanofibrous dressing. To make the yarns, kaolin with weight ratio of 5% was added to PVA/chitosan polymer blend and subsequently formed into nanofibres using the electrospinning method. Scaffolds were evaluated for to their microstructure, mechanical properties, surface wettability, water vapour transmission rate, water-uptake capacity, blood uptake capacity, blood compatibility, microbial penetration test, the number of colonies, and cellular response with the L929 cell line. Rats with full-thickness excisional wounds were treated with kaolin-containing and kaolin-free dressings. Results: The study showed that rats treated with the kaolin-incorporated mats demonstrated a significant closure to nearly 97.62±4.81% after 14 days compared with PVA/chitosan and the sterile gauze, which showed 86.15±8.11% and 78.50±4.22% of wound closure, respectively. The histopathological studies showed that in the PVA/chitosan/kaolin group, dense and regular collagen fibres were formed, while wounds treated with sterile gauze or PVA/chitosan scaffolds had random and loose collagen fibres. Conclusion: Our results show the potential applicability of PVA/chitosan/kaolin scaffolds as a wound care material.